2013
DOI: 10.1063/1.4826526
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of nanocrystalline SiGe alloys using molecular dynamics simulations

Abstract: We have studied the effect of nanocrystalline microstructure on the thermal conductivity of SiGe alloys using molecular dynamics simulations. Nanograins are modeled using both the coincidence site lattice and the Voronoi tessellation methods, and the thermal conductivity is computed using the Green-Kubo formalism. We analyze the dependence of the thermal conductivity with temperature, grain size L, and misorientation angle. We find a power dependence of L1/4 of the thermal conductivity with the grain size, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…Ideal Reyleigh scattering (n = 4) corresponds to α = 7/4 and produces the κ ∼ L 1/4 trend previously reported in molecular dynamics simulations [24]. It also offers a good approximation for the AlGaN results presented here (α 1.72).…”
supporting
confidence: 54%
“…Ideal Reyleigh scattering (n = 4) corresponds to α = 7/4 and produces the κ ∼ L 1/4 trend previously reported in molecular dynamics simulations [24]. It also offers a good approximation for the AlGaN results presented here (α 1.72).…”
supporting
confidence: 54%
“…Previous studies have shown that decreasing the grain size can effectively reduce the thermal conductivity. 15,16 The decreasing trend of thermal conductivity as grain size decreases in Fig. 4(c) confirm this observation.…”
Section: Resultssupporting
confidence: 72%
“…The MFP can be also calculated from l ¼ v g s, which must result in same value. Therefore, the relaxation time was estimated from the latter relation, which agrees with the decay of the autocorrelation of the average heat flux versus time for each material system, 34,35 such as the plot shown in Figure 4. According to kinetic relaxation time approximation, the thermal conductivity depends on the lattice specific heat per unit volume, average phonon group velocity, and the phonon mean free path.…”
Section: Discussion and Resultsmentioning
confidence: 99%